Water-repellent modification method for small-dip-angle rock or concrete surface layer

By using composite water repellent and dynamic heating technology, a dense water repellent layer is formed, which solves the problems of easy coating peeling, insufficient pore filling and poor durability in the water repellent treatment of rock or concrete surfaces, and achieves efficient water repellent performance and long-term protection effects.

CN119841665APending Publication Date: 2025-04-18BEIBU GULF UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510043998.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art has problems such as easy coating to fall off, insufficient pore filling, uneven water repellent properties and poor durability in complex environments in the water repellent treatment of rock or concrete surfaces.

Method used

A composite water repellent, including octadecyl primary amine, trifluoropropyltriethoxysilane, nanosilica and rare earth oxide, is used to form a dense water repellent layer through pretreatment, spreading, dynamic heating and cooling and curing steps.

Benefits of technology

It significantly improves the water repellent performance, enhances the density of the water repellent layer and the bonding strength of the substrate, solves the problems of insufficient durability and poor adhesion of the coating, and improves the service life and environmental adaptability in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841665A_ABST
    Figure CN119841665A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of rock or concrete surface modification, and discloses a small-dip-angle rock or concrete surface water repellent modification method which comprises the following steps: preparing a composite water repellent agent; pretreating the rock or concrete surface layer; a composite water repellent is spread on the pretreated surface layer; dynamically heating the paved and scattered composite water repellent agent; cooling and curing the surface layer. Preferably, the preparation of the composite water repellent agent comprises the following steps: taking octadecyl primary amine powder as a main body material, and adding the octadecyl primary amine powder into the composite water repellent agent with the mass ratio of 50-70%; adding trifluoropropyl triethoxy silane, wherein the mass ratio of the trifluoropropyl triethoxy silane to the triethoxy silane is 5-15%; adding nano silicon dioxide particles, wherein the mass ratio is 2-10%; graphene oxide is added, and the mass ratio is 0.5-3%; and adding the modified poly silicon powder. Through optimal design of the composite water repellent and combination of dynamic heating and cooling solidification, efficient permeation, uniform distribution and long-acting and durable protection effects of the water repellent layer are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rock or concrete surface modification, in particular to a method for water-repellent modification of a rock or concrete surface with a small inclination angle. Background Art

[0002] In the fields of modern construction engineering, heritage protection and marine engineering, waterproofing and water-repellent treatment of rock and concrete surfaces are of great significance. Due to their high porosity, rocks and concrete are very easy to absorb water, causing damage to the internal structure. For example, the steel bars in the concrete will be corroded faster due to water erosion, and the rock surface will be weathered and cracked due to long-term water intrusion, which directly affects the durability and safety of the structure. In addition, in heritage protection, the erosion of natural rock structures by water may cause irreversible damage to cultural heritage. Therefore, a method for water-repellent modification of the surface of small-angle rocks or concrete can achieve water blocking, prevent water erosion, and extend the service life of the substrate through effective surface water-repellent treatment.

[0003] In the prior art, common surface water-repellent treatment methods mainly include surface coating technology and overall doping technology. Surface coating technology can reduce the water absorption rate of the substrate to a certain extent and delay water intrusion by applying a thin film coating on the surface of the substrate. The overall doping technology directly adds water repellent during concrete preparation to make the entire concrete structure have a certain water resistance. These two methods have achieved certain results in certain application scenarios. For example, coating technology can form a surface protective film in a short period of time, with simple construction and low cost; while doping technology can significantly enhance the overall water resistance of concrete and is suitable for newly cast concrete components.

[0004] However, the above technical solutions still have many deficiencies in practical applications, which limits their further promotion. Although the surface coating technology can be waterproof in the short term, the physical adhesion of the coating is low and it is easy to fall off due to external conditions such as ultraviolet rays, humid and hot environments, resulting in rapid attenuation of the subsequent protection effect. In addition, due to the thin coating, the pore filling effect of porous materials is insufficient and it is impossible to completely prevent water penetration. The overall doping technology is only applicable to newly prepared concrete materials and cannot be used to treat natural rocks or formed concrete. At the same time, the doping technology requires a large amount of water repellent to be dispersed throughout the substrate, resulting in high material consumption and economic costs. More importantly, these existing technologies lack long-term protective performance in complex environments (such as high humidity, ultraviolet exposure, and alternating hot and cold environments), which can easily lead to coating failure or structural performance degradation. Therefore, it is difficult for existing technologies to fully meet the durability, protection and applicability requirements in actual engineering, and these deficiencies need to be solved urgently. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a method for water-repellent modification of the surface of rock or concrete with a small inclination angle, which solves the problems in the prior art of easy detachment of the coating, insufficient pore filling, uneven water-repellent performance and poor durability in complex environments.

[0006] To achieve the above purpose, the present invention is implemented by the following technical scheme: a method for water-repellent modification of a small-angle rock or concrete surface, comprising the following steps:

[0007] Preparation of composite water repellent;

[0008] Pre-treatment of rock or concrete surface;

[0009] Spread a composite water repellent on the pretreated surface;

[0010] Dynamically heating the composite water-repellent after spreading;

[0011] Cool and solidify the surface.

[0012] Preferably, the preparation of the composite water repellent comprises:

[0013] Octadecyl primary amine powder is used as the main material and added into the composite water repellent with a mass ratio of 50-70%.

[0014] Add trifluoropropyltriethoxysilane in a mass ratio of 5 to 15%;

[0015] Add nano silicon dioxide particles at a mass ratio of 2 to 10%;

[0016] Adding graphene oxide in a mass ratio of 0.5 to 3%;

[0017] Add modified polysiloxane at a mass ratio of 5 to 20%;

[0018] Add rare earth oxides at a mass ratio of 0.5 to 5%;

[0019] The above components are dissolved and dispersed in an ethanol solution, and composite powder with a particle size of 10 to 30 μm is prepared by spray drying.

[0020] Preferably, the pretreatment of the rock or concrete surface comprises:

[0021] Use 5% dilute hydrochloric acid solution to spray the surface, the reaction time is 10 to 15 minutes, and then rinse with deionized water and dry;

[0022] Use 10% sodium hydroxide solution to spray the surface for 10 to 15 minutes to further dissolve the minerals and form a rough microstructure on the surface, then rinse with deionized water and dry;

[0023] Spray 3% KH-570 silane coupling agent ethanol solution on the surface and let it stand for 20 to 30 minutes.

[0024] Preferably, the step of spreading the composite water repellent on the pretreated surface further comprises:

[0025] Spread composite water-repellent powder evenly on the surface, with a powder layer thickness of 3 to 5 mm;

[0026] Use a scraper to adjust the powder thickness to ensure uniformity;

[0027] The surface layer was divided into 20 cm × 20 cm grid units, and the composite powder was spread independently in each unit to avoid boundary overlap.

[0028] Preferably, the dynamically heating the spread composite water repellent comprises:

[0029] Cover the composite water repellent powder layer with a PET plastic film having a thickness of 0.1 mm;

[0030] Arrange flexible heating strips on the plastic film with a spacing of 20 cm between the heating strips and fix them with fixing tapes;

[0031] The temperature of the heating strip is adjusted by the temperature control module to maintain at 70-85°C, and the heating time is 30-60 minutes;

[0032] During the heating process, mechanical vibration with a vibration frequency of 10 to 20 Hz and an amplitude of less than 1 mm is applied to promote uniform penetration and melting diffusion of the powder.

[0033] Preferably, the cooling and solidifying surface layer comprises:

[0034] After heating is completed, turn off the heating device and cover with insulation cloth to prevent rapid cooling;

[0035] Cool naturally to room temperature within 12 hours;

[0036] The cooled surface layer is irradiated with an ultraviolet curing lamp having a wavelength of 350 to 400 nm for 10 to 15 minutes to further cross-link the composite water repellent.

[0037] Preferably, the composite water repellent further comprises fluorinated polymer particles added in a mass ratio of 1 to 5% to further reduce the surface energy of the surface layer.

[0038] Preferably, the pretreatment of the rock or concrete surface further includes preliminary roughening of the surface by mechanical sandblasting, with the roughness being controlled within a range of 1 to 10 μm.

[0039] Preferably, the dynamic heating further comprises using an infrared heater instead of the flexible heating strip, with a heating power of 300-500W, a distance of 10-20cm from the surface of the powder layer, and a temperature control range of 70-85°C.

[0040] Preferably, the cooling and curing is further cooled by low-temperature air circulation, the temperature of the cooling medium is controlled at 10 to 20° C., and the cooling time is 2 to 3 hours.

[0041] The present invention provides a method for water-repellent modification of small-angle rock or concrete surface, which has the following beneficial effects:

[0042] 1. The present invention adopts a unique composite water repellent formula design, combines core ingredients such as octadecyl primary amine, trifluoropropyl triethoxysilane, and the auxiliary effects of nano-silicon dioxide and rare earth oxides, and significantly enhances the water repellency. The powder has excellent low surface energy characteristics and uniform distribution. Compared with the existing single coating material solution, it solves the problems of insufficient durability and weak adhesion of the water repellent layer.

[0043] 2. The present invention uses a flexible heating strip for dynamic heating, and cooperates with a mechanical vibration device to achieve rapid diffusion of the powder after melting and fill the surface pores by improving both the heating uniformity and the powder penetration effect. Compared with the traditional fixed heating method, it avoids the problems of local overheating and incomplete penetration, and significantly improves the density of the water-repellent layer and the bonding strength of the substrate.

[0044] 3. The cooling process combines natural cooling with ultraviolet light-assisted curing. The present invention controls the cooling speed by covering with thermal insulation cloth and uses ultraviolet light to promote chemical cross-linking to ensure that the chemical bonding of the water-repellent layer is sufficient and the structure is uniform. Compared with the existing natural cooling method, the problem of stress concentration and insufficient stability during the curing process of the water-repellent layer is solved, and the overall service life and environmental adaptability are further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 The present invention is a flow chart of the method. DETAILED DESCRIPTION

[0046] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Please refer to the attached Figure 1 The embodiment of the present invention provides a method for water-repellent modification of a rock or concrete surface with a small inclination angle, comprising the following steps:

[0048] S1. preparing a composite water repellent;

[0049] This embodiment adopts multi-component compounding technology to achieve multi-functional synergy of surface water repellency. The present invention ensures that the prepared water repellent has excellent performance and is suitable for use in complex environments by accurately controlling the component ratio and preparation parameters.

[0050] In general, a composite water repellent needs to contain a material with low surface energy as a core component, supplemented with a functional filler that enhances roughness and mechanical properties. In the present invention, octadecyl primary amine is selected as the main material, and trifluoropropyl triethoxysilane (TFPES) is combined to further reduce the surface energy. In addition, nano-silicon dioxide is added to enhance the microscopic roughness, while graphene oxide (GO) and modified polysiloxane are used to improve the crack resistance and flexibility of the water repellent layer. In order to further enhance the anti-aging properties of the material, rare earth oxides (such as CeO2) are also added as functional additives.

[0051] In this embodiment, the preparation method of the composite water repellent is as follows:

[0052] First, prepare solution A. Add trifluoropropyltriethoxysilane in a mass ratio of 5-15% to a mixed solution of anhydrous ethanol and deionized water (volume ratio 1:1), and stir evenly at room temperature. The stirring speed is recommended to be controlled at 300-500 rpm for 10-15 minutes to ensure the uniformity of the solution. As an option, it can be operated by a magnetic stirrer to improve the stirring efficiency.

[0053] Next, add nano-silicon dioxide particles to solution A at a mass ratio of 2-10%. In order to obtain a uniform dispersion effect, an ultrasonic dispersion device can be used. The ultrasonic power is generally 100-150W, and the treatment time is 10-20 minutes. During the ultrasonic treatment process, the temperature of the solution can be appropriately increased (it is recommended to be controlled at 30-40°C) to improve the dispersion state of the nanoparticles.

[0054] Then, graphene oxide (GO) is gradually added to the uniformly dispersed solution, and the mass ratio is controlled at 0.5-3%. The addition of GO can improve the crack resistance of the composite water repellent and improve the mechanical properties. In a possible implementation, the mixed solution can be stirred by a high-speed shearing device, and the shearing speed is recommended to be controlled at 6000-8000rpm for 20-30 minutes. The purpose of the shearing operation is to evenly disperse GO in the solution to prevent it from agglomerating.

[0055] In this embodiment, octadecyl primary amine powder is used as the main material and is slowly added to the above-mentioned stirred and mixed solution at a mass ratio of 50-70%. Stirring needs to be maintained during the addition process, and the stirring speed is recommended to be 200-400 rpm for 15-20 minutes. As an option, the temperature can be gradually increased during the stirring process (not exceeding 40° C.) to enhance the dispersion effect of the powder.

[0056] Next, add modified polysiloxane (5-20% by mass) to the mixed system and continue stirring for 20-30 minutes to fully mix it with the main components. At this stage, pay attention to controlling the viscosity of the system. Too high viscosity may cause uneven particles in the subsequent drying process.

[0057] Finally, rare earth oxide (such as CeO2) is added at a mass ratio of 0.5-5%. Rare earth oxide can significantly improve the UV resistance and anti-aging performance of the water-repellent layer. In one embodiment, stirring can be continued for 10-15 minutes by a high-speed stirrer to ensure that the rare earth oxide is evenly dispersed.

[0058] After the above mixing is completed, the obtained slurry is dried by spray drying equipment. Generally, the inlet air temperature of spray drying is controlled at 110-130°C, and the outlet air temperature is 60-80°C. During the spray drying process, the feed rate is recommended to be controlled at 5-10mL / min to ensure the uniform particle size of the dried particles. After drying, a composite water-repellent powder with a particle size of 10-30μm can be obtained. As an option, the powder can be graded by a screening device to remove particles that are too large or too small.

[0059] In one possible implementation, the following formula can be used to optimize the component ratio:

[0060] W=w 主材 +w 改性剂 +w 填充剂 +w 助剂

[0061] Wherein, W is the total mass of the composite water repellent; w 主材 is the mass of octadecyl primary amine, ranging from 50% to 70%; w 改性剂 is the mass of trifluoropropyltriethoxysilane, ranging from 5% to 15%; w 填充剂 Including nano-silicon dioxide and graphene oxide, the total value range is 2.5% to 13%; w 助剂 For modified polysiloxane and rare earth oxide, the total value range is 5.5% to 25%.

[0062] In the above method, the prepared composite water repellent has good dispersibility and uniformity through the combination of solution dispersion technology and spray drying technology. Further screening operation ensures that the particle size range of the powder meets specific requirements. This material preparation method has high practicality and repeatability in industrial production, and can meet the requirements of the water repellent modification method of small-angle rock or concrete surface;

[0063] S2. Pre-treat the surface of rock or concrete;

[0064] Pretreatment can not only clean the surface, but also provide active sites through chemical and physical means to increase the surface roughness and adhesion. Generally, this step includes acid-base treatment and chemical activation treatment. As an option, in some embodiments, pretreatment can also be combined with mechanical roughening to meet more demanding application scenarios.

[0065] In this embodiment, the pretreatment method for the surface of rock or concrete is mainly divided into the following steps: acid treatment, alkali treatment and chemical activation treatment of silane coupling agent.

[0066] In this embodiment, the purpose of the acid treatment is to remove surface pollutants and loose particles, while exposing more hydroxyl (-OH) groups to promote subsequent chemical bonding. In general, the acid treatment is carried out using a dilute hydrochloric acid solution. Specifically, a 5% dilute hydrochloric acid solution is evenly sprayed on the surface of the rock or concrete, and the reaction time is 10 to 15 minutes. During the reaction, hydrochloric acid reacts with calcifications and alkaline impurities on the surface of the substrate to generate soluble salts. For the residue after the reaction, rinse the treated surface with deionized water to ensure that the salt substances are completely removed. As an option, air flow can be used to dry the surface after rinsing to prevent the influence of residual moisture on subsequent treatment.

[0067] Alkali treatment is to further dissolve the surface minerals and increase the micro-roughness of the surface. Generally, a 10% sodium hydroxide solution is used as an alkali treatment agent. Specifically, the sodium hydroxide solution is evenly sprayed on the surface of the acid-treated substrate, and the reaction time is 10 to 15 minutes. During this process, the alkali solution reacts with silica, silicates and other components in the surface layer to form a micron-sized rough structure. These microstructures can significantly improve the adhesion of subsequent water repellents. In one possible implementation method, deionized water is also used for rinsing after the alkali treatment is completed to ensure that the alkaline residues are completely removed. For some special rock materials (such as high-density granite), the alkali treatment time can be appropriately extended to 20 minutes to enhance the treatment effect.

[0068] After completing the acid-base treatment and ensuring the surface is clean, the chemical activation treatment of the silane coupling agent is carried out. Specifically, a 3% KH-570 silane coupling agent ethanol solution is selected and evenly covered on the surface of the substrate by spraying. Generally, the silane coupling agent can undergo a hydrolysis reaction at room temperature, forming a chemical bond with the exposed hydroxyl groups on the surface to generate a stable silicon-oxygen bond. As an option, in some embodiments, the activation time can be increased (20 to 30 minutes) to ensure that the silane coupling agent is fully reacted. For the reacted surface, avoid rinsing with water, but dry it directly or dry it with low-temperature air.

[0069] In one possible implementation, in order to further improve the surface roughness and bonding strength, the pretreatment can be combined with mechanical sandblasting. Mechanical sandblasting usually uses quartz sand with a particle size of 50 to 150 μm as an abrasive, and roughens the surface of the substrate by high-pressure spraying. The air pressure of the sandblasting operation is generally controlled at 0.3 to 0.6 MPa, and the sandblasting distance is 10 to 20 cm. Through sandblasting, a more uniform micron-level rough structure can be formed, while removing residual oxides and aging layers on the surface of the substrate;

[0070] In the above pretreatment process, the surface roughness can be characterized by the following formula:

[0071]

[0072] Among them, R a It represents the average roughness of the surface in micrometers (μm); L is the surface measurement length; Z(x) is the height value of a point on the surface; Z m In the pretreatment method of the present invention, the roughness range is generally controlled to be 1-10 μm, and the specific value is adjusted according to the material and the requirements of the subsequent steps.

[0073] In some embodiments, for porous concrete materials, the acid-base treatment can be repeated twice to ensure that the pollutants and impurities in the pores are completely removed. For rock materials with a large surface density (such as marble), the acid-base treatment time can be appropriately extended to 20 minutes. In addition, the surface must be dry after treatment, and residual moisture will directly affect the adhesion and penetration effect of the subsequent water repellent.

[0074] S3, spreading a composite water repellent on the pretreated surface;

[0075] By evenly spreading the prepared composite water repellent on the surface of the pretreated substrate, it is ensured that the water repellent can fully cover the target area, laying the foundation for subsequent dynamic heating and melting diffusion. Generally, this step requires special attention to the uniformity of the spreading thickness and the distribution range of the powder to ensure the integrity and performance consistency of the subsequent water repellent layer. As an option, some embodiments will perform zoning operations by dividing the area to improve the accuracy of spreading.

[0076] In this embodiment, the specific operation of spreading the composite water repellent on the pretreated surface is as follows:

[0077] In general, the thickness range of the composite water repellent powder needs to be determined according to the actual conditions of the substrate surface. Specifically, it is recommended to control the thickness of the composite powder to 3-5 mm. The choice of thickness is not only related to the roughness and porosity of the substrate, but also needs to consider the melting and diffusion behavior of the material during the subsequent dynamic heating process. In one possible implementation, a rock substrate with a lower roughness (such as marble) can be spread with a thinner powder layer, while for a porous concrete surface, the spreading thickness needs to be appropriately increased to fill the surface micropores.

[0078] In this embodiment, the composite water repellent powder is evenly spread on the surface. The specific operation steps include: first, using a quantitative powder spreading device to gradually add powder to the surface of the substrate. It is recommended that the moving speed of the powder spreading device be controlled at 10 to 15 cm / s to ensure the uniformity of powder distribution. As an option, the thickness of the powder can also be adjusted by manual operation combined with a scraper tool, especially when there are surface depressions in local areas.

[0079] In the process of spreading powder, the surface of the substrate can be partitioned. Specifically, the surface of the substrate can be divided into several regular grid units, and the side length of each unit is recommended to be set to 20 to 30 cm. Through partitioning, accumulation or uneven distribution of the edge of the powder layer can be avoided. In one possible implementation method, a transparent film can be used to mark the partition range, and powder spreading operations can be performed independently on each unit in turn. Partitioning not only helps to improve operational accuracy, but also effectively control material usage and reduce waste.

[0080] During the spreading process, attention should be paid to the particle distribution characteristics of the powder. Generally, the particle size of the composite water repellent powder is 10 to 30 μm. Too large a particle size range will lead to uneven spreading, while too small particles may be disturbed by vibration or airflow during subsequent operations and dispersed. Therefore, in order to ensure the distribution consistency of powder particles, the distribution of particles can be characterized by the following formula:

[0081] D 10 ,D 50 ,D 90

[0082] Among them, D 10 ,D 50 ,D 90 They represent the particle sizes corresponding to 10%, 50%, and 90% of the cumulative volume distribution in the particle distribution. For this embodiment, it is recommended to control the D 50 In the range of 15 to 20 μm, D 90 The particle size should not exceed 20 μm to ensure a moderate distribution range of particles.

[0083] In one embodiment, to further improve the spreading efficiency, an electrostatic auxiliary device can be set on the surface of the substrate. Through electrostatic assistance, the powder can be more stably attached to the surface of the substrate to avoid interference from environmental wind or vibration during operation. It is recommended that the electrostatic voltage be controlled at 5 to 10 kV, and the specific value is adjusted according to the environmental humidity and substrate characteristics.

[0084] As an option, for surfaces with an inclined angle (inclination angle greater than 10°), an adhesive lining cloth can be used to cover the surface of the substrate to fix the position of the powder layer. This method can effectively prevent the powder from sliding along the inclined direction during the spreading process. The material of the adhesive lining cloth is recommended to be PET film, with a thickness of 0.1 to 0.2 mm and a certain degree of air permeability to facilitate subsequent heating operations.

[0085] After the above steps are completed, the thickness uniformity of the powder layer can be checked by a laser thickness measuring device. In general, the thickness deviation should not exceed ±10%. The scanning speed of the laser thickness measuring device is recommended to be set to 20-30cm / s, and the scanning accuracy is ±0.1mm. Through inspection, it can be found whether the powder in a local area is too thick or too thin, and timely adjustments can be made;

[0086] S4, dynamically heating the composite water repellent after spreading;

[0087] Through dynamic heating, the composite water repellent melts and penetrates into the pores of the surface layer of the substrate under controlled temperature conditions, and physical and chemical reactions occur simultaneously to form a stable water repellent layer. In general, heating needs to ensure uniformity to prevent local overheating or unmelted problems. As an option, mechanical vibration technology can be combined to further promote the diffusion and penetration of the molten material, thereby improving the overall uniformity and stability of the water repellent layer.

[0088] In this embodiment, the specific method of dynamically heating the composite water repellent after spreading is as follows:

[0089] In this embodiment, the heating device is arranged on the surface of the powder using a flexible heating strip, which is connected to an external power source and adjusts the heating parameters through a temperature control module. In general, the spacing of the flexible heating strips is recommended to be controlled at 20 cm, which can cover the entire powder spreading area and provide uniform heat distribution. As an option, the arrangement of the heating strips can also be appropriately adjusted according to the inclination of the surface of the substrate, such as increasing the density of the heating strips in the inclined area to compensate for the natural diffusion loss of heat.

[0090] Specifically, the temperature setting range of the heating strip is 70-85°C, and the selection of this range is based on the melting characteristics of the composite water repellent and the heat resistance of the substrate. The melting point of octadecyl primary amine is around 70°C, while trifluoropropyltriethoxysilane and modified polysiloxane can maintain chemical stability within this temperature range and can react chemically with the active groups on the surface of the substrate. In one possible implementation, the temperature control module can dynamically adjust the heating parameters according to the real-time monitored surface temperature to ensure that the temperature of the entire heating area is evenly distributed, and the maximum temperature difference does not exceed ±5°C.

[0091] During the heating process, in order to promote the melting and diffusion of the composite water repellent, a mechanical vibration device can be combined. Generally, it is recommended to set the vibration frequency to 10-20 Hz and control the amplitude to 0.5-1 mm. The role of vibration is to reduce the surface tension of the molten water repellent through physical disturbance, so that it can diffuse and penetrate into the micropores of the substrate more quickly. As an option, a multi-frequency vibration method can be used in some embodiments to adapt to powder layers of different thicknesses and substrate pore structures.

[0092] In one possible implementation, in order to further optimize the melting and diffusion process, a 0.1mm thick PET plastic film can be covered between the heating strip and the powder layer. The PET film has two main functions: one is to prevent the powder from directly contacting the heating strip to avoid local overheating; the other is to further improve the uniformity of temperature distribution in the entire heating area by evenly conducting heat.

[0093] For dynamic heating time control, 30 to 60 minutes is generally recommended. The choice of time mainly depends on the thickness of the powder layer and the thermal conductivity of the substrate. Specifically, for a powder layer with a thickness of 3 to 4 mm, a heating time of 30 minutes can usually meet the melting requirements; for a powder layer with a thickness of more than 5 mm, the heating time can be appropriately extended to more than 50 minutes. In one embodiment, the relationship between heating time and temperature can be estimated by the following formula:

[0094]

[0095] Where t is the heating time in seconds; ρ is the density of the composite powder in kg / m 3; c is the specific heat capacity, in J / (kg·K); ΔT is the temperature rise, in k; h is the thickness of the powder layer, in m; k is the thermal conductivity, in W / (m·K); A is the heating area, in m 2 .

[0096] In the above formula, the parameters ρ and c are determined by the component ratio of the composite water repellent. For example, the density of octadecyl primary amine is 0.81 g / cm 3 , the specific heat capacity is 1460 J / (kg·K). By adjusting the heating temperature ΔT and time t, the melting optimization of powder layers of different thicknesses can be achieved.

[0097] In a specific embodiment, an infrared thermal imager can be used to monitor the temperature distribution of the heating area in real time. The resolution of the infrared thermal imager is recommended to be ±0.1°C and the scanning frequency is 10Hz. Through thermal imaging monitoring, local overheating or unheated areas can be discovered in time and compensated by adjusting the power of the heating strip.

[0098] As an option, for special environments (such as high humidity or low temperature conditions), hot air auxiliary equipment can be added during the heating process. The hot air temperature is recommended to be controlled at 50-60°C and the wind speed is 25m / s. The main function of hot air is to accelerate the heat exchange process on the surface of the powder, while preventing the interference of environmental humidity on the heating effect;

[0099] S5, cooling and solidifying the surface layer;

[0100] By natural cooling, controlling the cooling rate and UV-assisted curing, the composite water repellent can be fully combined with the surface of the substrate to form a dense water repellent layer structure. Generally, this step requires special attention to the uniform temperature drop and the full progress of the chemical reaction to ensure the mechanical properties and chemical stability of the water repellent layer. As an option, some embodiments will be combined with a thermal protection device or external cooling measures to meet the processing requirements under different environmental conditions.

[0101] In this embodiment, the method of cooling and curing the surface layer is as follows:

[0102] In this embodiment, after the dynamic heating is completed, the heating device is first turned off, and the surface of the powder is kept free from external disturbances. In general, the surface directly exposed to the environment may increase the internal stress of the material due to a sudden drop in temperature, thereby causing cracks or uneven solidification. Therefore, as an option, a layer of insulation cloth can be covered to control the cooling rate. Specifically, the insulation cloth is recommended to be made of polyester fiber material with a thickness of 5mm, which can effectively reduce the interference of the ambient temperature difference on the cooling process of the powder layer.

[0103] During the natural cooling process, the temperature drop rate is recommended to be controlled at 2 to 5°C / min. Specifically, a slower cooling rate can avoid stress concentration caused by temperature gradients during powder solidification. In one possible implementation, an infrared thermometer can be combined to monitor changes in surface temperature in real time. The measurement accuracy of the infrared thermometer is recommended to be ±0.1°C, the measurement frequency is 10Hz, and it can provide continuous temperature change data. Through the temperature measurement data, it can be judged whether the cooling process is as expected, and the thickness of the covering insulation cloth or other auxiliary measures can be adjusted in time.

[0104] As an option, for thinner powder layers (thickness less than 3mm), cooling can be accelerated by increasing air circulation. Specifically, a low-speed fan can be used to deliver room temperature air to the cooling area. The wind speed is recommended to be controlled at 12m / s to ensure that the air flow does not disturb the stability of the powder layer. At the same time, for thicker powder layers (thickness exceeding 5mm), it is recommended to use a more uniform cooling method, such as transferring temperature through liquid cooling equipment. The temperature of the liquid cooling medium is recommended to be controlled at 20-30°C, and the entire surface is evenly covered by spraying.

[0105] During the cooling and curing process, the chemical reaction of the composite water repellent will further proceed, especially the chemical bonding reaction between trifluoropropyltriethoxysilane and the surface of the substrate. In a possible implementation, the chemical curing reaction mechanism of the surface water repellent is described by the following equation:

[0106] R-Si(OR′)3+H2O→R-Si(OH)3+ROHR

[0107] R-Si(OH)3+-OH 基材 →R-Si-O 基材 +H2O

[0108] Wherein, R represents a trifluoropropyl structure, R' is an ethoxy group, -OH 基材 Indicates the exposed hydroxyl groups on the surface of the substrate. During the cooling process, these chemical reactions will be gradually completed to form a stable silicon-oxygen bond structure, providing excellent chemical bonding for the water-repellent layer.

[0109] After natural cooling is completed, in order to further improve the compactness and stability of the water-repellent layer, ultraviolet light curing is used for auxiliary treatment in this embodiment. Specifically, a UV curing lamp with a wavelength of 350 to 400 nm is used to evenly irradiate the surface layer. The role of ultraviolet light is to activate the silane groups and polysiloxane groups that have not fully reacted in the composite water-repellent and promote their further cross-linking. In general, it is recommended that the ultraviolet light irradiation time be controlled within 10 to 15 minutes, and the power of the light source is recommended to be 100 to 150W. As an option, the irradiation effect of ultraviolet light can be optimized by adjusting the distance between the light source and the surface layer (recommended to be 10 to 20 cm).

[0110] During the UV curing process, the curing effect can be evaluated by monitoring the change in the contact angle of the water-repellent layer. Generally, the contact angle of the water-repellent layer should gradually reach a stable value (usually ≥160°). The change trend of the contact angle can be described by the following formula:

[0111]

[0112] Where θ represents the contact angle; γ SG , γ SL , γ LG They represent the solid-gas interfacial tension, solid-liquid interfacial tension and liquid-gas interfacial tension respectively. After UV curing is completed, the interfacial tension parameters of the surface layer will reach a stable state, thus forming efficient water-repellent properties.

[0113] As an example, for low temperature environments (ambient temperature below 10°C), additional thermal protection measures may be required during the cooling process. For example, an electric heating film can be added under the insulation cloth to maintain the minimum temperature of the powder surface at no less than 15°C. The power of the electric heating film is recommended to be 50-100W / m 2 , and combined with the temperature control module for real-time adjustment.

[0114] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for water-repellent modification of small-angle rock or concrete surface, characterized in that: The following steps are involved: Preparation of composite water repellent; Pre-treatment of rock or concrete surface; Spread a composite water repellent on the pretreated surface; Dynamically heating the composite water-repellent after spreading; Cool and solidify the surface.

2. A method for water-repellent modification of a small-angle rock or concrete surface according to claim 1, characterized in that: The preparation of the composite water repellent comprises: Octadecyl primary amine powder is used as the main material and added into the composite water repellent with a mass ratio of 50-70%. Add trifluoropropyltriethoxysilane in a mass ratio of 5 to 15%; Add nano silicon dioxide particles at a mass ratio of 2 to 10%; Adding graphene oxide in a mass ratio of 0.5 to 3%; Add modified polysiloxane at a mass ratio of 5 to 20%; Add rare earth oxides at a mass ratio of 0.5 to 5%; The above components are dissolved and dispersed in an ethanol solution, and composite powder with a particle size of 10 to 30 μm is prepared by spray drying.

3. A method for water-repellent modification of a small-angle rock or concrete surface according to claim 1, characterized in that: The pretreatment of the rock or concrete surface layer comprises: Use 5% dilute hydrochloric acid solution to spray the surface, the reaction time is 10 to 15 minutes, and then rinse with deionized water and dry; Use 10% sodium hydroxide solution to spray the surface for 10 to 15 minutes to further dissolve the minerals and form a rough microstructure on the surface, then rinse with deionized water and dry; Spray 3% KH-570 silane coupling agent ethanol solution on the surface and let it stand for 20 to 30 minutes.

4. A method for water-repellent modification of a small-angle rock or concrete surface according to claim 1, characterized in that: The method of spreading the composite water repellent on the pretreated surface further comprises: Spread composite water-repellent powder evenly on the surface, with a powder layer thickness of 3 to 5 mm; Use a scraper to adjust the powder thickness to ensure uniformity; The surface layer was divided into 20 cm × 20 cm grid units, and the composite powder was spread independently in each unit to avoid boundary overlap.

5. The method for water-repellent modification of a rock or concrete surface with a small inclination angle according to claim 1, characterized in that: The dynamically heating the composite water repellent after spreading comprises: Cover the composite water repellent powder layer with a PET plastic film having a thickness of 0.1 mm; Arrange flexible heating strips on the plastic film with a spacing of 20 cm between the heating strips and fix them with fixing tapes; The temperature of the heating strip is adjusted by the temperature control module to maintain at 70-85°C, and the heating time is 30-60 minutes; During the heating process, mechanical vibration with a vibration frequency of 10 to 20 Hz and an amplitude of less than 1 mm is applied to promote uniform penetration and melting diffusion of the powder.

6. A method for water-repellent modification of a small-angle rock or concrete surface according to claim 1, characterized in that: The cooling and solidifying surface layer comprises: After heating is completed, turn off the heating device and cover with insulation cloth to prevent rapid cooling; Cool naturally to room temperature within 12 hours; The cooled surface layer is irradiated with an ultraviolet curing lamp having a wavelength of 350 to 400 nm for 10 to 15 minutes to further cross-link the composite water repellent.

7. A method for water-repellent modification of a small-angle rock or concrete surface according to claim 2, characterized in that: The composite water repellent further comprises fluorinated polymer particles added in a mass ratio of 1-5% to further reduce the surface energy of the surface layer.

8. The method for water-repellent modification of a rock or concrete surface with a small inclination angle according to claim 3, characterized in that: The pretreatment of the rock or concrete surface further includes preliminary roughening of the surface by mechanical sandblasting, with the roughness being controlled within a range of 1 to 10 μm.

9. A method for water-repellent modification of a rock or concrete surface with a small inclination angle according to claim 5, characterized in that: The dynamic heating further includes using an infrared heater instead of the flexible heating strip, with a heating power of 300-500W, a distance of 10-20cm from the surface of the powder layer, and a temperature control range of 70-85°C.

10. A method for water-repellent modification of a small-angle rock or concrete surface according to claim 6, characterized in that: The cooling and solidification is further cooled by low-temperature air circulation, the temperature of the cooling medium is controlled at 10-20° C., and the cooling time is 2-3 hours.